The Ecological Significance of Plant Growth Promoting Rhizobacteria in Tropical Soil Kalimantan: A Narrative Review: Plant Growth Promoting Rhizobacteria in Tropical Soil Kalimantan - Ervinda Yuliatin; Lutfi Fadhlillah; Ivoryta Arinda; Imam Rosadi; Nova Hariani; Linda Oktavianingsih (Journal of Tropical Life Science, 2023)
The diversity of flora in Kalimantan influences the presence of microbe-associated with rhizosphere on their activities and functions in ecosystems. However, abiotic stress such as acidification, drought, and toxic soil residues negatively impacted soil health and plant growth in some regions of Kalimantan's soil. The rhizobacteria, as a group of the plant-growth-promoting rhizobacteria (PGPR), can colonize in the rhizosphere to produce their natural product in making phytohormone for root growth, maintaining soil aggregation and solubilizing the mineral in the soil. Those benefit of rhizobacteria is essential to investigate. However, the study of the role of rhizobacteria in Kalimantan soil interaction with the plant was unclear. Therefore, this review focused on the presence of rhizobacteria and their potency to solve abiotic problems in Kalimantan soil and the underlying mechanism rhizobacteria employs to tolerate harsh soil.